Mereformasi Pendidikan : Mengkaji Rendahnya Kemampuan Berpikir Kritis Siswa melalui Pendekatan Pendidikan Kritis Ivan Illich - Hayail Umroh; Syamsul Rijal; Firdaus M. Yunus (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The lack of critical thinking skills among students is one of the major issues in modern education systems. This study aims to analyze the weaknesses of traditional education systems that fail to provide space for the development of students' critical thinking skills and explore the relevance of Ivan Illich's critical education approach. This research employs a qualitative method with a literature review approach to understand Illich's Deschooling Society concept and connect it to educational phenomena in Indonesia, such as the Merdeka Curriculum, homeschooling, and project-based schools. The findings show that Illich's critical education approach can be applied to modern education systems to create more inclusive, flexible, and empowering learning environments. Illich's learning webs concept is relevant for enhancing student engagement in learning and building their critical thinking abilities. This study recommends educational reform that focuses on individual empowerment, creativity development, and improving analytical skills to face global challenges.